Tb0.3Dy0.7Fe1.9/PbZr0.52Ti0.48O3 Micro-Bridge on SiNx Thin Film for Low Frequency Magnetic Sensing Applications - Lee, Dong Gun; Han, Jun Hyun; Lee, Junwoo; Choi, Wook; Yoo, Yong Kyung; Kim, Jinseok; Hwang, Kyo Seon; Kim, Tae Song; Chun, Dong Won; Kim, Yu-Chan; Lee, Kyu Hyoung; Lee, Jeong Hoon (IOP PUBLISHING LTD, 2013)
A micro-fabricated bridge sensor for determining minute magnetic field variation is proposed. A micro-bridge with 100 x 400 mu m(2) dimensions (width x length) comprises a multi-layered structure of Tb0.3Dy0.7Fe1.9/PbZr0.52Ti0.48O3 on a SiNx supporting layer. We observed the limit of detection under small DC magnetic field as 1 x 10(-11) T which was converted electrically to 77 mu V with a 5 mu V noise floor via elastic coupling between magnetostrictive and piezoelectric thin film. The magnetoelectric (ME) voltage was linearly proportional to small magnetic field variance, and the experimental ME coefficient was measured as 9.9 V/(cm.Oe). (C) 2013 The Japan Society of Applied Physics
Keywords: COMPOSITES